PARENTAL ENGAGEMENT AS A CATALYST FOR ACADEMIC SUCCESS AND EMOTIONAL DEVELOPMENT IN STUDENTS: A LITERATURE REVIEW - Jain, Bhawna; Puri, Jyoti (International Journal of Research -GRANTHAALAYAH, 2025)
Parental involvement has emerged as a critical factor influencing students' educational outcomes and psychological well-being. This comprehensive review examines the existing literature on how parental engagement affects emotional stability and academic success among students across different educational levels. Through systematic analysis of 85 peer-reviewed studies published between 2010 and 2023, this review identifies key mechanisms through which parental involvement operates, examines various forms of parental engagement, and synthesizes findings on their differential impacts. The evidence consistently demonstrates positive correlations between active parental involvement and improved academic performance, enhanced emotional regulation, and better social adjustment. However, the quality and type of involvement matter more than quantity, with authoritative parenting styles and academic support showing the strongest associations with positive outcomes. Over the past decade, both indigenous and foreign research has thrown light on various outcomes of parental involvement, focusing on its forms, emotional influence, impact on academic performance, and the socio-cultural factors that shape students' lives. A reiterated theme across studies is the positive correlation between active parental engagement and students’ emotional well-being and scholastic improvements. Despite these benefits, emerging challenges such as cultural disparities, low economic background, and increasing digital distractions complicate the regular involvement of parents with their children. This review underscores how patterns of parental participation vary across cultural contexts and how these differences influence their effectiveness. The insights gained have meaningful implications for shaping educational policies, enhancing school-family collaboration, and developing targeted interventions. The paper concludes with practical recommendations and avenues for future research.